Patient-Specific Approach to Mitral Valve Replacement in Infants Weighing 10 kilograms or less. Issue 3 (May 2019) - Mater, Kathryn; Ayer, Julian; Nicholson, Ian; Winlaw, David; Chard, Richard; Orr, Yishay
Background: Mitral valve replacement (MVR) is the only option for infants with severe mitral valve disease that is not reparable; however, previously reported outcomes are not always favorable. Our institution has followed a tailored approach to sizing and positioning of mechanical valve prostheses in infants requiring MVR in order to obtain optimal outcomes. Methods: Outcomes for 22 infants ≤10 kg who have undergone MVR in Sydney, Australia, from 1998 to 2016, were analyzed. Patients were at a mean age of 6.8 ± 4.1 months (range: 0.8-13.2 months) and a mean weight of 5.4 ± 1.8 kg at the time of MVR. Most patients (81.8%) had undergone at least one previous cardiac surgical procedure prior to MVR, and 36.4% had undergone two previous procedures. Several surgical techniques were used to implant mechanical bileaflet prostheses. Results: All patients received bileaflet mechanical prostheses, with 12 receiving mitral prostheses and 10 receiving inverted aortic prostheses. Surgical technique varied between patients with valves implanted intra-annularly (n = 6), supra-annularly (n = 11), or supra-annularly with a tilt (n = 5). After a mean follow-up period of 6.2 ± 4.4 years, the survival rate was 100%. Six (27.3%) patients underwent redo MVR a mean of 102.2 ± 10.7 months after initial MVR. Four (18.2%) patients required surgical reintervention for development of left ventricular outflow tract obstruction and three (13.6%) patients required permanent pacemaker placement during long-term follow-up. Conclusions: The tailored surgical strategy utilized for MVR in infants at our institution has resulted in reliable valve function and excellent survival. Although redo is inevitable due to somatic growth, the bileaflet mechanical prostheses used displayed appropriate durability.